The Correlation Between Self-Assessment and Observation in Driving Style Classification: An On-Road Case Study - Muhammad Zainul Abidin Kamaludin; Juffrizal Karjanto; Noryani Muhammad; Nidzamuddin Md Yusof; Muhammad Zahir Hassan; Mohamad Zairi Baharom; Zulhaidi Mohd Jawi; Matthias Rauterberg (Information, 2025)
A typical classification of driving style from a human driver is conducted via self-assessment, which begs the question of the possibility of bias from the respondents. Although some research has been carried out validating the questionnaire, no controlled studies have yet to be reported to validate the Malaysian driving style. This study aimed to validate the Malaysian driver using the Multidimensional Driving Style Inventory (MDSI) with five-factor driving styles (careful, risky, angry, anxious, and dissociative) in on-road situations. Forty-one respondents completed the experiment on two designated routes recorded over 45 min of driving. A modest correlation existed between the MDSI and the score retrieved from the on-road observation assessment. The result showed a low-to-medium correlation collected from acceleration in longitudinal directions compared with correlation analysis utilizing the MDSI scale. Exploring such latent traits is essential for precisely classifying human driver styles without bias.